2013
DOI: 10.1590/s0034-71672013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida no trabalho e burnout em trabalhadores de enfermagem de Unidade de Terapia Intensiva

Abstract: Estudo descritivo, correlacional, de corte transversal, cujos objetivos foram avaliar a Qualidade de Vida no Trabalho (QVT) e a presença da Síndrome de Burnout entre profissionais de enfermagem de Unidade de Terapia Intensiva. Compuseram a amostra 53 trabalhadores de enfermagem de um hospital escola do interior do Paraná, Brasil. Utilizou-se para a coleta de dados: instrumento de caracterização sócio-demográfica e profissional, Escala Visual Analógica para QVT e o Maslach Burnout Inventory (MBI). A coleta de d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
55

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 14 publications
1
26
0
55
Order By: Relevance
“…The version of the MBI used consisted of a five-point Likert scale (1)(2)(3)(4)(5) , different from the original instrument with seven categories. The choice for this version of the instrument was due to the difficulties observed among Brazilian respondents to discriminate the seven categories of the original instrument (11) .…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The version of the MBI used consisted of a five-point Likert scale (1)(2)(3)(4)(5) , different from the original instrument with seven categories. The choice for this version of the instrument was due to the difficulties observed among Brazilian respondents to discriminate the seven categories of the original instrument (11) .…”
Section: Study Protocolmentioning
confidence: 99%
“…It has negative socioeconomic consequences and affects the worker's physical and mental health (1)(2)(3) . This condition has been reported among nursing professionals, who are often in contexts of dynamic work, overburden and intense interpersonal relationships, which makes them susceptible to developing Burnout (1)(2)4) . It is important to deepen the understanding of the factors associated with this syndrome in order to find strategies to prevent it, which would benefit the health of the worker and the quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Many times, these characteristics can present factors or circumstances that affect the health and quality of life (QOL) of professionals working in these environments (3)(4)(5)(6)(7)(8)(9) . Quality of life is a term that has been explored in several studies with a wide range of concepts.…”
Section: Introductionmentioning
confidence: 99%
“…From the analysis of studies, the main factors identified as responsible for the psychic and moral exhaustion were moral distress (7,13,(17)(18)(19) and burnout syndrome (2,5,7,(20)(21)(22) . The analyzed studies were performed mainly with nurses, and describe moral distress and Burnout as frequent phenomena in the reality of different health work contexts.…”
Section: Resultsmentioning
confidence: 99%